2000
DOI: 10.21273/horttech.10.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Benefits to Human Well-being of Urban Gardens

Abstract: ADDITIONAL INDEX WORDS. gardening, greenspace, horticultural therapy, restorative environment, urban food production, urban sustainability SUMMARY. Private gardens occupy a significant proportion of the total surface area of a British city. For many people, the garden represents their only contact with nature and their chance to express themselves creatively. Yet relatively little research has been carried out on the role and value of such gardens to human well-being. We report in this paper on a major survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 10 publications
9
69
1
3
Order By: Relevance
“…Thus the results of the study need to be interpreted in this context. Nevertheless, it is also clear that a substantial majority of UK residents invests time and interest in the garden: a random survey of Sheffield garden owners indicated that more than 75% enjoyed their garden environment, while less than 10% valued nothing about their garden (Dunnett and Qasim 2000). Our experience also revealed that owners' interest in the project or in wildlife issues did not necessarily match effort spent on the garden, due to constraints on time such as young children or a busy job.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Thus the results of the study need to be interpreted in this context. Nevertheless, it is also clear that a substantial majority of UK residents invests time and interest in the garden: a random survey of Sheffield garden owners indicated that more than 75% enjoyed their garden environment, while less than 10% valued nothing about their garden (Dunnett and Qasim 2000). Our experience also revealed that owners' interest in the project or in wildlife issues did not necessarily match effort spent on the garden, due to constraints on time such as young children or a busy job.…”
Section: Discussionmentioning
confidence: 78%
“…We therefore believe that our approach allowed us to survey the full range of variation in interest and creativity one might expect to encounter in a random sample (and possibly more): from gardens used daily to those largely untouched for 10 years; from gardens including wildlife meadows and ponds to those with nothing but a lawn. Further, our sample contained the full span of garden sizes as found in a random sample (Dunnett and Qasim 2000), which permitted us fully to investigate landcover in relation to garden area. For the twenty-two invertebrate taxa examined, a broad range of factors were significantly related to their abundance in gardens.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the extent, composition and access to green spaces within urban areas have been shown to have significant impacts on the quality of life of urban populations. First, evidence is gathering in support of benefits for human physical and mental well-being (Ulrich 1998;Dunnett and Quasim 2000;Takano et al 2002;CABE Space 2004;Galea et al 2005). Second, benefits are evident through a diverse array of economic impacts, including those on house prices, the costs of heating and cooling buildings, and the ease of attracting businesses and employees to areas (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This quality can have significant impacts on (a) the physical and mental well-being of the people living and working in these areas (e.g. Ulrich 1984;Dunnett and Quasim 2000;Takano et al 2002;CABE Space 2004;Galea et al 2005); (b) urban economies, through a diverse array of impacts, including on house prices, the costs of heating and cooling buildings, and the ease of attracting businesses and employees (e.g. Luttik 2000;Morancho 2003;CABE Space 2004); and (c) the provision both of ecosystem services (e.g.…”
Section: Introductionmentioning
confidence: 99%